Women, sustainable entrepreneurship and the economy : a global perspective - Caliyurt, Kiymet Tunca; Segura, Liliane (Women and sustainable business., 2020)
When a woman decides to become an entrepreneur, she starts her business with a sense of excitement, freedom, wealth, happiness, prestige; however, these feelings can soon turn to fears over debt, difficulties, unpaid invoices, stress, and uncertainty. Being an entrepreneur means taking risks, making decisions, adapting management styles in line with developmental needs, clashing with rivals, being more agile than competitors, negotiating risky scenarios, following business trends, capturing new opportunities before, and being better than the competition. If a woman wants to be successful as an entrepreneur, she needs to have a business education, undergo continued professional development, and have patience and emotional intelligence. Supporting women in their entrepreneurial activities has been shown to positively affect the economy, which is why governments pay special attention to opening new funding opportunities and training programs for women who want to start or develop a business. Female entrepreneurship has individual characteristics because of those aspects of the business which are affected by cultural, technological, legislative, social, and historical developments. This book discusses the relationship between female entrepreneurship and the economy, and academic authors from developing countries such as Brazil, Turkey, Albania, Kosovo, Portugal, and Malaysia analyze the developments encompassing women and entrepreneurship in their respective countries. The authors discuss the regulatory frameworks of each country to show how these either help or hinder female entrepreneurship, and consequently, the place of women in the economy. Women and entrepreneurship is an emerging theme, and this book is a must-read for researchers from both developing and developed countries.